Maxillary Impacted Canines: A Clinical Review - Yadav, Rajiv; Shrestha, Basanta K (Orthodontic Journal of Nepal, 2013)
Impacted teeth are those with a delayed eruption time or that are not expected to erupt completely based on clinical and radiographic assessment. Palatal displacement of the maxillary canines is defined as the developmental dislocation to a palatal site often resulting in tooth impaction requiring surgical and orthodontic treatments. Impacted permanent maxillary canine occur in 1-2% of the population. The Occurrence of impacted permanent maxillary canines are; 85% palatal and 15% labial. The prevalence of palatally displaced canines (PDC) fluctuates between 0.8-5.2%. Palatally erupting or impacted maxillary canines occur twice often in females than males, and are five times more common in Caucasians than Asians. Of all patients with maxillary impacted canines, 8% have bilateral impactions. DOI: http://dx.doi.org/10.3126/ojn.v3i1.9285 Orthodontic Journal of Nepal, Vol.3, No.1, 2013: 63-68